2013
DOI: 10.1111/apa.12227
|View full text |Cite
|
Sign up to set email alerts
|

Differences in parents', nurses' and physicians' views of NICU parent support

Abstract: NICU nurses and physicians should be encouraged to critically reflect on whether the type and consistency of support they provide to parents is in line with parents' perceptions and needs. Further research is needed on effective methods for health professionals to support parents of NICU infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
50
5
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 27 publications
7
50
5
3
Order By: Relevance
“…One of the most important aspects to consider in FCC culture is the position of staff in relation to the parents and their perceived expectations of involvement [16,33,34]. Inadequate staffparent interaction and communication can exacerbate parents' sense of isolation from their premature infants [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important aspects to consider in FCC culture is the position of staff in relation to the parents and their perceived expectations of involvement [16,33,34]. Inadequate staffparent interaction and communication can exacerbate parents' sense of isolation from their premature infants [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The focus of the medical team was on providing information on the baby’s clinical status and on the care required. Clinical information is one of the principal forms of support given by physicians to the mothers of babies hospitalized in an NICU [16, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these HCPs were aware of the difficulties involved in taking on the role of facilitators of the development of the early relationship between parents and their infants [14, 15]. There are reports that refer that HCPs often provide instrumental support and technical care that, albeit necessary and indeed vital for the babies’ recovery, does not focus on the desires and needs of the parents, frequently marginalizing their role during the hospitalization period [5, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…(13-17)Our primary perception outcome measure was self-reported happiness to care for a THAPCA patient. We evaluated association of the measure with nurse characteristics (demographics, education, participation in past research activities), self-reported confidence in research skills, perceived study team support, training and work burden, and the importance of the THAPCA research hypothesis.…”
Section: Introductionmentioning
confidence: 99%